Assessing the fetal effects of maternal obesity via transcriptomic analysis of cord blood: a prospective case–control study. (January 2016) - Edlow, AG; Hui, L; Wick, HC; Fried, I; Bianchi, DW
Abstract : Objective: To analyse fetal gene expression at term using umbilical cord blood, in order to provide insights into the effects of maternal obesity on human development. Design: Prospective case–control study. Setting: Academic tertiary care centre. Population: Eight obese (body mass index ≥30 kg/m 2 ) and eight lean (body mass index <25 kg/m 2 ) pregnant women undergoing prelabour caesarean delivery at term. Methods: Women were matched for gestational age and fetal sex. Cord blood RNA was extracted and hybridised to gene expression arrays. Differentially regulated genes were identified using paired t ‐tests and the Benjamini–Hochberg correction. Functional analyses were performed using Ingenuity Pathway Analysis, BioGPS and Gene Set Enrichment Analysis with a fetal‐specific annotation. Z ‐scores ≥2.0 or P ‐values <0.01 were considered significant. Main outcome measure: Functions of differentially regulated genes in fetuses of obese women. Results: A total of 701 differentially regulated genes were identified, producing an expression profile implicating neurodegeneration, decreased survival of sensory neurons, and decreased neurogenesis in the fetuses of obese women. Upstream regulators related to inflammatory signalling were significantly activated; those related to insulin receptor signalling, lipid homeostasis, regulation of axonal guidance, and cellular response to oxidative stress were significantly inhibited. Of 26 tissue‐specific genes that were differentially regulated in fetuses of obese women, six mapped to the fetal brain. Conclusion: Maternal obesity affects fetal gene expression at term, implicating dysregulated brain development, inflammatory and immune signalling, glucose and lipid homeostasis, and oxidative stress. This may have implications for postnatal neurodevelopment and metabolism. Tweetable abstract: Fetal cord blood transcriptome in obese women suggests neurodevelopmental and metabolic programming effects. Tweetable abstract: Fetal cord blood transcriptome in obese women suggests neurodevelopmental and metabolic programming effects.